2015
DOI: 10.1002/chin.201525085
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Enantioselective Conjugate Additions of α‐Amino Radicals via Cooperative Photoredox and Lewis Acid Catalysis.

Abstract: Enantioselective Conjugate Additions of -Amino Radicals via CooperativePhotoredox and Lewis Acid Catalysis. -The first highly enantioselective intermolecular addition of photogenerated -amino radicals to Michael acceptors is reported. This new method features a dual-catalyst protocol that combines transition metal photoredox catalysis with chiral Lewis acid catalysis which provides an effective, general strategy to generate and control the reactivity of photogenerated reactive intermediates. Efficient remova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The overall mechanism of α-amino functionalization likely follows the sequence outlined by Pandey, Reiser 8 and Yoon 9 . Irradiation of the Ir catalyst generates an excited state complex that is capable of accepting an electron from the amine substrate to form an ammonium radical cation.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The overall mechanism of α-amino functionalization likely follows the sequence outlined by Pandey, Reiser 8 and Yoon 9 . Irradiation of the Ir catalyst generates an excited state complex that is capable of accepting an electron from the amine substrate to form an ammonium radical cation.…”
mentioning
confidence: 88%
“…Photocatalytic strategies provide mild methods to form and functionalize carbon-centered radicals. 7 For example, the Pandey and Reiser groups 8 and the Yoon group 9 independently described the formation of α-ainino radicals 2 derived from tetrahydroisoquinolines in the presence of a Ru(bpy) 3 2+ photocatalyst (Scheme 1A). Similarly, Nicewicz showed that symmetrical carbamates could be alkylated with electron poor olefins 10 in the presence of an organic photocatalyst (Scheme 2B).…”
mentioning
confidence: 99%
“…In 2015, Yoon reported the conjugate addition of α-aminoalkyl radicals to α,β-unsaturated pyrazolidinones under photoredox conditions, reaching enantioselectivitites of up to 96% ee (Figure 1a). 5 The dualcatalysis strategy uses [Ru(bpy) 3 ]Cl 2 as the photoredox catalyst to convert α-silylalkyl anilines into free radicals, while a Sc(III)/Pybox complex serves as the chiral Lewis acid to catalyze the radical conjugate addition and to provide the asymmetric induction. However, high loadings of the Sc(III)based Lewis acid are required, and the method is limited to αsilylalkyl anilines as radical precursors.…”
Section: ■ Introductionmentioning
confidence: 99%